2011
DOI: 10.1007/s10195-011-0128-0
|View full text |Cite
|
Sign up to set email alerts
|

Titanium elastic nailing versus hip spica cast in treatment of femoral-shaft fractures in children

Abstract: BackgroundThere is no consensus on treatment of closed femoral-shaft fractures in children. We compared hip spica cast with titanium elastic nailing (TEN) in the treatment of femoral-shaft fractures in children.Materials and methodsForty-six children, 6–12 years old, with simple femoral-shaft fractures were randomized to receive skeletal traction followed by hip spica cast (n = 23) or TEN (n = 23). Length of hospital stay, time to start walking with aids, time to start independent walking, time absent from sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 12 publications
10
42
0
Order By: Relevance
“…Our study showed male predominance in both groups and this was comparable to the studies published by Shemshaki H. R. et al [2], Saseendar S. et al [3] and Jauquier N. et al [6]. Regarding fracture site, our study showed middle third predominance in both groups and this is comparable with the studies published by Shemshaki et al [2], Jauquier N. et al [3] and Nicolas Lutz et al [4].…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Our study showed male predominance in both groups and this was comparable to the studies published by Shemshaki H. R. et al [2], Saseendar S. et al [3] and Jauquier N. et al [6]. Regarding fracture site, our study showed middle third predominance in both groups and this is comparable with the studies published by Shemshaki et al [2], Jauquier N. et al [3] and Nicolas Lutz et al [4].…”
Section: Resultssupporting
confidence: 82%
“…Regarding fracture site, our study showed middle third predominance in both groups and this is comparable with the studies published by Shemshaki et al [2], Jauquier N. et al [3] and Nicolas Lutz et al [4]. Our study sample showed highly significant.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…For older children, an important study in 2010 by Shemshaki et al compared the use of titanium elastic nailing (TEN) to hip spica casting in 46 patients, aged 6 to 12 years, with simple femur fractures [24]. Compared to patients treated with a spica cast, those treated with TEN had shorter hospital stays, took a shorter time to start walking, returned to school sooner, had a lower rate of malunion, and had higher parent satisfaction.…”
Section: Spica Castingmentioning
confidence: 99%